Association of life's essential 8 with chronic cardiovascular-kidney disorder: a prospective cohort study - Xinghe Huang; Jie Liang; Junyu Zhang; Jiayi Fu; Sicheng Deng; Wuxiang Xie; Fanfan Zheng (BMC, 2024)
Abstract Background The coexistence of cardiovascular disease and chronic kidney disease, termed chronic cardiovascular-kidney disorder (CCV-KD), is increasingly prevalent. However, limited studies have assessed the association between cardiovascular health (CVH), assessed by the American Heart Association's Life's Essential 8 (LE8), and CCV-KD. Methods We conducted a prospective cohort study using data from UK Biobank. Participants without cardiovascular disease and chronic kidney disease at baseline and having complete data on metrics of LE8 were included (N = 125,986). LE8 included eight metrics, and the aggregate score was categorized as low (< 50 points), intermediate (50 to < 80 points), and high (≥ 80 points), with a higher score indicating better CVH health. Adjusted Cox proportional hazard models were conducted to explore the association of CVH with the risk of CCV-KD. The adjusted proportion of population attributable risk (PAR%) was used to calculate the population-level risk caused by low or intermediate CVH. Results During a median follow-up of 12.5 years, 1,054 participants (0.8%) had incident CCV-KD. Participants with intermediate and high CVH had 54% (HR = 0.46, 95% CI: 0.40-0.54, P < 0.001) and 75% (HR = 0.25, 95% CI: 0.18-0.34, P < 0.001) lower risks of incident CCV-KD compared with those in low CVH group. There was an approximately dose-response linear relationship between the overall LE8 score and incident CCV-KD. The risk of incident CCV-KD decreased by 30% (HR = 0.70, 95% CI: 0.67-0.74, P < 0.001) for a 10-point increment of LE8 score. The adjusted PAR% of lower overall CVH was 47.4% (95% CI: 31.6%-59.8%). Conclusions Better CVH, assessed by using LE8 score, was strongly associated with decreased risk of incident CCV-KD. These findings imply optimizing CVH may be a preventive strategy to reduce the burden of CCV-KD.